DEVELOPMENT AND VALIDATION OF DERIVATIVE SPECTOSCOPIC METHODFOR SIMULTANEOUS DETERMINATION OF NEBIVOLOL HYDROCHLORIDE AND S-AMLODIPINE BESYLATE IN COMBINED DOSAGE FORM - DR. ATUL PATEL (International Journal of Pharma and Bio Sciences, 2013)
A novel, simple, accurate, sensitive, reproducible, economical spectroscopic method has been developed and validated for the determination of Nebivolol hydrochloride and S-amlodipine besylate in combined dosage form. The method obeys Beer’s Law in concentration range of 15-35 µg/ml for Nebivolol and 7.5-17.5 µg/ml for S-amlodipine. The method was validated for linearity, range, accuracy, precision and specificity as per ICH guidelines. Zero crossing point for Nebivolol hydrochloride and S-amlodipine besylate was 243 nm and 291 nm respectively in methanol. The developed method as successfully used for the quantitative analysis of commercially available dosage form (Nebicard SM).